A Comparison of Pediatric and Adult Safety Studies for Antipsychotic and Antidepressant Drugs Submitted to the United States Food and Drug Administration - Liu, Xiaomei I.; Schuette, Paul; Burckart, Gilbert J.; Green, Dionna J.; La, Julie; Burnham, Janelle M.; Rakhmanina, Natella; Robb, Adelaide; Huang, Shiew Mei; van den Anker, John N. (The Journal of pediatrics, 2019)
To examine the differences in the adverse drug reaction (ADR) profile of antipsychotic and antidepressant agents between pediatric and adult patients in studies submitted to the Food and Drug Administration (FDA) during the drug development process. Clinical trials in adult and pediatric patients were conducted by sponsors as part of the drug development programs for antipsychotic and antidepressant agents, and ADR information was collected as part of those trials and submitted to the FDA. Data collection was conducted by reviewing publicly available FDA-authored reviews and FDA-approved product labels for 10 drugs with an antipsychotic or an antidepressant indication from 2007 to 2017. There were 308 drug and ADR combinations for the 10 drugs and drug combinations with 113 (36.7%) having a significantly different incidence in pediatric patients compared with adults. Sixty-eight (60.2%) of these ADRs had a significantly higher incidence in pediatric patients than in adults. Sedation was higher in 6 of the 10 drugs and drug combinations with risk differences ranging from 9.6 to 36.6%. This analysis indicates that there were significant differences between the pediatric and adult safety profiles of antipsychotic and antidepressant drugs. Sedation was the major ADR associated with the use of atypical antipsychotic drugs in pediatric patients. Clinicians caring for children should consider the ADR profile when prescribing antipsychotics and antidepressants in pediatric patients.